Percepção de sustentabilidade na visão dos alunos das engenharias do campus Pau dos Ferros - Barboza, Beatriz de Souza (Universidade Federal Rural do Semi-Árido, 2019)
In recent years society has been increasingly concerned about the environment due to the environmental changes that the planet has undergone. The term sustainability emerges in this context of concern for the environment, accelerated technological development, increased consumption of natural resources and consequently increased environmental impacts. Thus, this study aims to analyze the perception of students of Engineering courses at the Rural University of Semi-Arid, Campus Pau dos Ferros regarding the sustainability theme and what is the impact on their professional performance, through bibliographic research related to the theme and application of questionnaires in the academic community. It was found that all students know the term sustainability, but do not know how to apply in their professional activities. Thus, it was found that even with the need to adapt to the changes that the planet has been going through, there is a large deficit in the training of engineering professionals committed to the environment.
Keywords: Profissionais de engenharia; Impactos ambientais; Instituição pública; Desenvolvimento econômico; Engineering professionals; Environmental impacts; Public Institution; Environment; Economic development; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA